2008
DOI: 10.1038/nature07668
|View full text |Cite
|
Sign up to set email alerts
|

WSTF regulates the H2A.X DNA damage response via a novel tyrosine kinase activity

Abstract: SummaryDNA double-stranded breaks present a serious challenge for eukaryotic cells. Inability to repair breaks leads to genomic instability, carcinogenesis, and cell death. During the DSB response, mammalian chromatin undergoes reorganization demarcated by H2A.X Ser139 phosphorylation (γ-H2A.X). However, the regulation of γ-H2A.X phosphorylation and its precise role in chromatin remodeling during the repair process remain unclear. Here, we report a novel regulatory mechanism mediated by WSTF, a component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
345
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(361 citation statements)
references
References 47 publications
13
345
1
2
Order By: Relevance
“…At the molecular level, it has been demonstrated that regulation of nucleosome deposition is essential for transcriptional activation or repression, 28 -30 DNA replication, 31,32 DNA damage repair, 4,33,34 and cell cycle progression. [35][36][37] Chromatin remodeling factors that control DNA winding/unwinding cycles are therefore believed to be involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, it has been demonstrated that regulation of nucleosome deposition is essential for transcriptional activation or repression, 28 -30 DNA replication, 31,32 DNA damage repair, 4,33,34 and cell cycle progression. [35][36][37] Chromatin remodeling factors that control DNA winding/unwinding cycles are therefore believed to be involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…DSBs are detected by the Mre11-Rad50-Nbs1 complex, which then recruits the ataxia-telangiectasia mutated (ATM) kinase, and post-translational modifications of the histone variant H2A.X occur in the surrounding chromatin [37,38]. These modifications act as a switch, either to promote recruitment of the repair machinery or to induce apoptosis.…”
Section: Generation Of Chromosome Rearrangementsmentioning
confidence: 99%
“…Phosphorylation of histone H2A at serine 129 enhances the recruitment of the INO80 complex to facilitate the repair of doublestrand DNA breaks (van Attikum et al, 2004). In mammalian cells, the Williams Syndrome Transcription Factor-SNF2H (Sucrose NonFermentable 2H) chromatin remodeling complex plays a vital role in the DNA damage response and phosphorylates tyrosine 142 of H2A.X (Xiao et al, 2009). In addition to DNA damage, phosphorylation of H2A at serine 121 by Bub1 (Budding Uninhibited By Benzimidazoles 1) regulates the localization of shugoshin to prevent chromosomal instability (Kawashima et al, 2010), and phosphorylation of histone H2A at tyrosine 56 by Casein Kinase II (CK2) regulates transcriptional elongation (Basnet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%